Variable lymphocyte receptor F is generated via somatic diversification and expressed by lamprey T-like cells - Sabyasachi Das; Francisco Fontenla-Iglesias; Masayuki Hirano; Ryo Morimoto; Byron B. Au-Yeung; Yashuo Wang; Weiming Li; Thomas Boehm; Jonathan P. Rast; Max D. Cooper (Nature Communications)
Abstract All extant jawless vertebrates (lampreys and hagfishes) possess a unique adaptive immune system characterized by highly variable lymphocyte receptors (VLR) that are assembled in developing lymphocytes using leucine-rich-repeat donor cassettes. Five VLR types have been identified in lampreys: VLRA, VLRB, VLRC, VLRD, and VLRE. VLRB-expressing lymphocytes are functional analogs to B cells, whereas VLRA, VLRC, VLRD, and VLRE-expressing lymphocytes are more akin to T cells of jawed vertebrates. Here we define an additional VLR, designated VLRF. VLRF is phylogenetically closest to VLRA, with which it likely shares a common ancestral gene of at least 250 million years in the past. VLR assembly analyses show that VLRA, VLRC, VLRD, VLRE, and VLRF share donor cassettes through long-range intra- and inter-chromosomal interactions, whereas VLRB utilizes a distinct, dedicated cassette set. The pattern of gene expression, donor cassette usage, and distinctive amino acid composition in the C-terminal stalk suggest that VLRF⁺ lymphocytes may represent an additional T-like sub-lineage, adding further complexity to the VLR-based adaptive immune system.